2021
DOI: 10.15414/jmbfs.5412
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antagonistic Effects of Some Bacillus Spp. On the Growth and Mycotoxin Production of Toxigenic Aspergilli

Abstract: This study aimed to investigate the antagonistic effect of three strains of the genus Bacillus on toxigenic fungi contaminating food commodities, with emphasis on two ochratoxigenic isolates (A. ochraceus, A. westerdijkiae) and two aflatoxigenic isolates (A. flavus and A. parasiticus). In vitro studies were carried out using two different methods for cultivation tested bacilli with fungal isolatescoincubation and dual culture method. The most sensitive isolate was A. ochraceus by both used methods. B. mycoides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Inhibition of mycotoxigenic fungi was also observed by the VOCs produced by B. megaterium KU143 and Pseudomonas protegens AS15 in the case of Aspergillus flavus , where the total aflatoxin production in rice grains was reduced by 90.4%, besides the reduced fungal population [ 52 ]. Hlebová et al [ 53 ] have shown complete inhibition of ochratoxin synthesis in Aspergillus ochraceus and Aspergillus westerdijkiae by VOCs produced by B. mycoides, B. subtilis, and B. thuringiensis . Acetoin was found to be the major VOC produced by B. velezensis G341, inhibiting mycelial growth of Sclerotinia sclerotiorum (cucumber Sclerotinia rot ), Rhizoctonia solani (rice sheath blight), and Botrytis cinerea (tomato grey mold) [ 54 ].…”
Section: Mechanisms Of Action Of Antifungal Bacillus ...mentioning
confidence: 99%
“…Inhibition of mycotoxigenic fungi was also observed by the VOCs produced by B. megaterium KU143 and Pseudomonas protegens AS15 in the case of Aspergillus flavus , where the total aflatoxin production in rice grains was reduced by 90.4%, besides the reduced fungal population [ 52 ]. Hlebová et al [ 53 ] have shown complete inhibition of ochratoxin synthesis in Aspergillus ochraceus and Aspergillus westerdijkiae by VOCs produced by B. mycoides, B. subtilis, and B. thuringiensis . Acetoin was found to be the major VOC produced by B. velezensis G341, inhibiting mycelial growth of Sclerotinia sclerotiorum (cucumber Sclerotinia rot ), Rhizoctonia solani (rice sheath blight), and Botrytis cinerea (tomato grey mold) [ 54 ].…”
Section: Mechanisms Of Action Of Antifungal Bacillus ...mentioning
confidence: 99%